2009
DOI: 10.1136/pgmj.2008.067975
|View full text |Cite
|
Sign up to set email alerts
|

Causes of mortality in diabetes mellitus: data from a tertiary teaching hospital in India

Abstract: Background: Mortality studies can show the relative contribution of diabetes to mortality in the total population, and they can provide important descriptions of the changes in causes and frequency of diabetes mortality over time. Objective: To find the mortality pattern in people with diabetes admitted to a tertiary care hospital in a developing country, using underlying/contributory causes of death. Methods: In this retrospective study, mortality trends among people with diabetes admitted to Sher-i-Kashmir I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 18 publications
9
32
2
1
Order By: Relevance
“…Mean age at death was 63.7 years (60.8 years in males and 66.5 years in females) in our study ,consistent with the finding of AH Zargar et al [8] and Chin Hsiao Tseng [45] for males but higher age at death in females was seen in their study. Mean HbA1c level among mortalities was 8.31 + 1.53.It was highest in patients who died of infections (8.47) and lowest in those who died of hypoglycaemia (6.67).…”
Section: Discussion:-supporting
confidence: 92%
See 2 more Smart Citations
“…Mean age at death was 63.7 years (60.8 years in males and 66.5 years in females) in our study ,consistent with the finding of AH Zargar et al [8] and Chin Hsiao Tseng [45] for males but higher age at death in females was seen in their study. Mean HbA1c level among mortalities was 8.31 + 1.53.It was highest in patients who died of infections (8.47) and lowest in those who died of hypoglycaemia (6.67).…”
Section: Discussion:-supporting
confidence: 92%
“…Renal failure (17.2%) and myocardial infarction (12%) in our study were other causes of mortality. Chronic renal failure contributed to 33.6% deaths in the study of AH Zargar et al In his study, coronary artery disease and cerebrovascular disease were responsible for 16.9% and 13.2% of deaths respectively [8]. Hypoglycemia was responsible for death in 5.1% patients in the present study.…”
Section: Discussion:-supporting
confidence: 46%
See 1 more Smart Citation
“…Hyperlipidemia was prevalent among 85.9% (165/192) of the study diabetics in India 8 and two studies done in India showed that diabetes related deaths in India is dominated by infections and renal failure unlike cardiovascular or cerebrovascular causes which dominate the developed countries. 9,10 The type 2 diabetes burden in India is escalating, more prevalent in the southern region of the country primarily due to changes in socioeconomic conditions, dietary habits and reduced physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…В связи с этим, основное значение для снижения смертности приобретают профилактические меропри-ятия, предупреждающие развитие ССЗ и включающие изменение образа жизни (отказ от курения, физиче-ская активность, диета), обучение в школах диабета, адекватное лечение и контроль уровня АД, глюкозы, лечение дислипидемий [34]. Снижение общей смерт-ности и смертности от ССЗ, заболевания почек, сеп-сиса, пневмонии, гриппа наблюдаются у больных СД c регулярными физическими нагрузками [45].…”
Section: факторы снижающие общую смертность при сахарном диабете 2 типаunclassified